Short Notices (Reviews in religion and theology, 2000)
Books reviewed in this article: Seth D. Kunin (ed.), Themes and Issues in Judaism Daniel J. Harrington, S.J., Invitation to the Apocrypha Jon Davies, Death, Burial and Rebirth in the Religions of Antiquity John Sawyer, Sacred Languages and Sacred Texts Donald H. Juel, The Gospel of Mark Peter Richardson, Herod: King of the Jews and Friend of the Romans Charles Carpenter, Theology as the Road to Holiness in St. Bonaventure Friedrich von Hügel, The Mystical Element of Religion As Studied in Saint Catherine of Genoa and her Friends Richard Cross, Duns Scotus Denis R. Janz (ed.), A Reformation Reader: Primary Texts with Introductions Carter Lindberg (ed.), The European Reformations Sourcebook Frank J. Coppa (ed.), Controversial Concordats: The Vatican's Relations with Napoleon, Mussolini, and Hitler Frank J. Coppa (ed.), Encyclopedia of the Vatican and Papacy Dorothy Day, On Pilgrimage Michael Jenkins, The Church Faces Death: Ecclesiology in a Post-Modern Context James L. Fredericks, Faith Among Faiths: Christian Theology and Non-Christian Religions Vinoth Ramachandra, Faiths in Conflict?: Christian Integrity in a Multicultural World Eric James, In Season, Out of Season John R. Tyson, Invitation to Christian Spirituality: An Ecumenical Anthology Donald Eadie, Grain in Winter Michael Welker, Creation and Reality